Secondhand smoke: A comparison of exposure to bar employees in a state with smoking bans and a state without smoking bans - Oluwapese M Akinbobola; Mac Crawford; Qinghua Sun (Wolters Kluwer Medknow Publications, 2016)
Background: Only 28 states have comprehensive laws prohibiting smoking in public places including all bars and restaurants. This project studied secondhand smoke (SHS) in bars in Covington, KY, where it is still legal to smoke indoors versus air quality in Cincinnati, OH bars where it is not legal to smoke indoors. Previous studies took samples from bars before and after smoking bans were put in place, but outdoor air quality in general could have changed in the areas over time. Materials and Methods: Air samples were taken in eight bars, four in Ohio where smoking is prohibited and four in Kentucky where smoking is permitted. All samples were taken on the same evening spending 30 min in each location with the instrument as close to the center of the room as possible. Results: Environmental conditions in Cincinnati, OH, and Covington, KY were very similar on the sampling evening. This along with the fact that the two cities are adjacent across the state line means that the bars in question should be subjected to similar outdoor air influences on air quality. However, the overall average time-weighted average (TWA) in Ohio was found to be 0.019 while the average TWA in Kentucky was 16 times higher at 0.303 mg/m 3 . Conclusion: Smoking bans have been shown to reduce the levels of exposure of SHS to the employees of bars and restaurants along with the patrons of these establishments. This reduces the risk of disease that may result from such exposure.